HLA-DR Genotyping and Mitochondrial DNA Analysis Reveal the Presence of Family Burials in a Fourth Century Romano-British Christian Cemetery - Voong, Canh P.; Spencer, Patrick S.; Navarrete, Cristina V.; Turner, David; Hayrabedyan, Soren B.; Crummy, Philip; Holloway, Emma; Wilson, Mike T.; Smith, Patricia R.; Fernández, Nelson (Frontiers in Genetics, 2017)
In Colchester, Britain’s oldest recorded town, during the Roman period there were areas which were clearly used solely as cemeteries. One of the most significant is at Butt Road, which includes a late Roman probable Christian cemetery with an associated apparent church building that overlies and developed from a pagan inhumation cemetery. DNA was extracted from the long bones (femurs) of 29 individuals, mostly from a large complex of burials centered on two timber vaults. These were thought to comprise a number of family groupings, deduced from osteological analysis, stratigraphical and other considerations. The use of a modified version of the silica-based purification method recovered nanogram quantities of DNA/gram of bone. Two-stage amplification, incorporating primer-extension preamplification-polymerase chain reaction, permitted simultaneous amplification of both mitochondrial and nuclear DNA. Sequence-specific oligonucleotide probes yielded human leukocyte antigen (HLA)-DR typing of seven samples, with four revealing the infrequent HLA-DR10 genotype. Examination of the control region of mitochondrial DNA (mtDNA) by direct sequencing revealed polymorphisms yet to be reported in the modern population. HLA-DRB typing and mtDNA analysis affirmatively supported kinship among some, if not all, individuals in the ‘vault complex’ and demonstrate a European origin of the individuals investigated.